Etika Berpacaran dalam Tinjuan Etika Kristen - Yufial Gulo; Helen Yohana Sinaga (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The author is interested in discussing the role of dating ethics in the review of Christian ethics. The importance of digging deeper into how dating ethics can be applied in the dynamics of today's life is the basis of this conversation.This journal aims to explore the ethics of dating not only to form, but also to strengthen the relationship between partners.Qualitative method is a scientific research that aims to understand a phenomenon in natural social contact by prioritizing the process of in-depth communication interaction between the researcher and the phenomenon to be discussed. Ethics is about what is good and right. Most people agree with the ethical values of honesty, keeping promises, respect, accepting mistakes, respecting human rights and taking responsibility. Dating ethics refers to the principles and practices that should be followed when in love. It includes qualities such as respect, honesty and commitment to the relationship. Dating rituals also include the responsibility to protect your partner's feelings and trust. You as well as avoid any actions that hurt or harm both parties in the relationship. Dating is an exploration between individuals, Creating love with human relationships also increases the motivation to learn, establish close friendships, and give heart. By following these principles, we can create strong and important relationships based on moral values blessed by the teachings of Christ.